Mathematical modelling of the traffic congestion problem at a University campus (2008)
"The traffic situation at many university campuses in developing countries has been a source of concern to both the school authority and the campus populace. This may be largely due to the increasing enrolment level for university admissions since most employers are certificate-biased instead of skill rewarding. The roads are often congested during the day thereby causing inconveniences to everyone. During the ""peak period"" when vehicular traffic is beyond what the road can contain conveniently, traffic jams occur, which accounts for a great amount of time wastage by commuters. This paper deals with the traffic congestion problem in a university in a developing country. The approach employs mathematical modeling to solve the problem. The principles of flow in fluid mechanics are interpreted at a macro level to the flow of traffic. The model describes the traffic situation, explains the causes and periods of congestion, and proffers a solution to the problem. "